Learn WebAssembly : build web applications with native performance using Wasm and C/C++ - Rourke, Mike (Packt Publishing Ltd, 2018)
WebAssembly is a brand new technology that represents a paradigm shift in web development. Learning WebAssembly will teach you how to leverage this technology to write performant applications that run in the browser. This book covers the history and underlying concepts of WebAssembly, before exploring getting a WASM module up and running.